Influence of Professional Practice Environment and Burnout on Job Satisfaction among Nurses in Ghana: Professional Practice Environment - Poku, Collins Atta; Donkor, Ernestina; Naab, Florence (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Background: Research on professional practice environment (PPE) is necessary in determining nursing job outcomes in every health organisation. Insight at the health care facilities can, however uncover key factors which induce burnout and its associated job dissatisfaction. The study investigated the influence of PPE and burnout on job satisfaction in the Ghanaian context. Materials and Methods: A cross-sectional approach with a sample of 232 Registered Nurses completed a questionnaire measuring PPE, burnout and job satisfaction. Descriptive, Pearson Correlation and Multilinear Regression analysis were done. Results: The findings revealed that nurses were generally satisfied with their PPE. Satisfaction with all aspects of their job were recorded except for pay/salary and standard of care given to patients. There were associations between PPE facets and job satisfaction. Multilinear models showed age of the nurse, years in nursing, staffing and resource adequacy, participation in hospital affairs, emotional exhaustion and personal accomplishment as predictors of nurses’ job satisfaction. Conclusion: The findings suggest that healthy PPE and reduced burnout improve the job satisfaction of nurses. Implications for Nursing Management: Health managers must ensure adequate nurses’ participation in hospital affairs and improvement in resource to reduce burnout and in effect enhance the overall PPE of nurses.